Multiscale methods bridging the scales in science and engineering - Fish, J. (Jacob) (Oxford : Oxford University Press, 2009)
This volume is intended as a reference book for scientists engineers and graduate students practicing in traditional engineering and science disciplines as well as in emerging fields of nanotechnology, biotechnology, microelectronics and energy.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Finite element method; Homogenization (Differential equations); Differential equations